A method for evaluating the corrosion resistance of oil well cement to carbon dioxide

Through comprehensive experimental and numerical simulation methods, the carbon dioxide corrosion resistance of oil well cement was comprehensively evaluated, which solved the problem of insufficient comprehensive evaluation in the existing technology, and improved the accuracy and speed of evaluation.

CN118376567BActive Publication Date: 2025-02-11INST OF ROCK & SOIL MECHANICS CHINESE ACAD OF SCI
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410608441.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-16
Publication Date
2025-02-11
Estimated Expiration
2044-05-16

AI Technical Summary

Technical Problem

The prior art is difficult to effectively evaluate the corrosion resistance of oil well cement, resulting in poor carbon storage sealing effect.

Method used

A comprehensive evaluation method is adopted, including sample preparation, long-term cement corrosion, microstructure and mechanical index testing, carbonization depth testing, numerical model establishment and comprehensive evaluation. By simulating the corrosion evolution of cement under the temperature and pressure of the formation, and combining mechanical, microstructure and numerical simulation results, the cement's corrosion resistance resistance is comprehensively evaluated.

Benefits of technology

The evaluation speed and accuracy of the corrosion resistance of carbon dioxide of oil well cement is significantly improved, and it can more comprehensively reflect the macroscopic and microscopic characteristics of cement, providing reasonable prediction and optimization suggestions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118376567B_ABST
    Figure CN118376567B_ABST
Patent Text Reader

Abstract

The present invention provides a method for evaluating the carbon dioxide corrosion resistance of oil well cement. The method comprises: (1) evaluating according to the variation law of mechanical indicators; (2) evaluating according to the variation law of microstructure; (3) evaluating according to the variation law of carbonation depth in numerical simulation. (4) comprehensive evaluation combining the variation law of mechanical indicators, microstructure and numerical simulation carbonation depth. The present invention can further improve the evaluation speed of the carbon dioxide corrosion resistance of oil well cement.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to two technical fields: cementing quality evaluation in the process of oil drilling and quality evaluation of cementing cement for long-term CO2 storage, and in particular relates to a method for evaluating the carbon dioxide corrosion resistance of oil well cement. Background Art

[0002] Although Li Guohua's "Evaluation Method of Cement Stone Corrosion by Wet CO2 at High Temperature" has written about the evaluation method, it does not involve numerical simulation methods, and has not established models and related theoretical formulas. The specific XRD method has not been described in depth, and its mechanical index only has compressive strength. Li Guohua's specific evaluation method: Use cement test blocks with Ф×h of "1×1" to evaluate the compressive strength, permeability, corrosion degree and anti-corrosion effect of cement stone. The cement slurry prepared according to the GB / T19139-2003 oil well cement test method is placed in a high temperature and high pressure curing kettle for curing to prepare cement test blocks. The prepared and numbered cement test blocks and corrosive media are placed in the CO2 corrosion instrument, and the pressure and temperature changes of the CO2 corrosion instrument are observed at any time, and adjusted in time. Under different corrosion conditions, the change law of the compressive strength and permeability of the corrosion sample and the relationship with the corrosion depth are measured; in order to obtain the influence of relevant influencing factors on the corrosion depth, the corrosion depth of the cement stone sample is measured under different conditions of constantly changing corrosion temperature and CO2 pressure divider corrosion time. The depth of CO2 corrosion on cement stone can be measured by wet CO2 technology. First, the CO2 crystal state and its content in cement are measured by quantitative X-ray diffraction method under different temperature and pressure conditions. Then, the corroded cement samples are tested by a special electron probe microanalysis method to measure the radial distribution thickness of the calcium carbonate layer generated after the cement stone samples are corroded by CO2 under different conditions, that is, the corrosion depth.

[0003] There is no implementation standard for domestic carbon storage well sealing. Drawing on the standards for abandoned wells in natural gas or gas storage, the pressure can meet the requirements, but the corrosiveness and penetration of CO2 will produce an "ant corrosion" effect on the original casing, resulting in failure of well sealing. In view of the above situation, it is necessary to analyze the key factors of sealing failure, design a sealing simulation evaluation method, and quantitatively evaluate the gas sealing performance and safe and effective period of the self-compensating well sealing process. As one of the important materials used in oil well cement stone well sealing, the carbon dioxide corrosion resistance of oil well cement is directly related to the carbon storage sealing effect, so there is an urgent need for an evaluation method for carbon dioxide corrosion resistance.

[0004] Based on the analysis of the chemical process of carbon dioxide corroding cement, the article "Corrosion of Oil Well Cement Stone" measured and analyzed the microstructure, compressive strength and permeability of corroded cement stone. It was found that the designed No. 6 cement had good performance at 120°C in terms of compressive strength and permeability, but there was no targeted research on XRD destroying the microstructure and changing the performance, and no evaluation method was mentioned.

[0005] The "Study on the Evaluation of Carbon Dioxide Corrosion on Oil Well Cement" establishes a rapid evaluation method for carbon dioxide corrosion on oil well cement through micro-concentrated sample tests. This method is used to evaluate the corrosion law of CO2 on oil well cement, providing sufficient theoretical basis and reliable experimental data for the selection of cement slurry systems suitable for CO2-rich oil and gas fields. The above evaluation method is an evaluation made within a relatively short period of time, and is mainly based on strength and permeability. Summary of the invention

[0006] The purpose of the present invention is to solve the defects of the above-mentioned prior art and provide a method for evaluating the anti-carbon dioxide corrosion performance of oil well cement, which can further improve the evaluation speed of the anti-carbon dioxide corrosion performance of oil well cement.

[0007] The present invention adopts the following technical solution:

[0008] A method for evaluating the carbon dioxide corrosion resistance of oil well cement, comprising:

[0009] Step (1). Sample preparation (or making samples according to the recipe), at least 3 samples of each type need to be prepared;

[0010] Step (2). Long-term corrosion of cement, the corrosion time is at least 7 days (put the sample into the reactor, pour in groundwater, cover the reactor, inject carbon dioxide into it, and then set the temperature and pressure of the corresponding formation. The temperature and pressure are set according to the working conditions. Because the capacity of the reactor is limited, the sample is made into a cylindrical sample with a diameter of 25mm and a height of 50mm as much as possible. The reactor can accommodate 75 samples at a time);

[0011] Step (3). Microstructure and mechanical index testing;

[0012] Step (4). Carbonization depth test;

[0013] Step (5). Establishing a numerical model;

[0014] Step (6). Comprehensive evaluation based on mechanical indicators, microstructure and numerical simulation of the change pattern of carbonization depth.

[0015] Furthermore, in step (3), the mechanical index test refers to analyzing the changes in physical and mechanical indexes such as breakthrough pressure, compression resistance, shear resistance, and tensile strength of oil well cement under simulated formation temperature and pressure conditions, analyzing the change patterns of various indexes with the concentration of carbon dioxide solution and the action time, and constructing a corrosion evolution model;

[0016] When the rate of decrease of mechanical indicators of cements with different formulations is stable, microstructural analysis is carried out;

[0017] Compressive strength, tensile strength and breakthrough pressure are obtained in the process.

[0018] Furthermore, in step (3), microstructure analysis refers to the study of the change law of microstructure analysis such as porosity, permeability and XRD test of oil well cement under simulated formation temperature and pressure conditions, and the analysis of the change law of various indicators with the concentration of carbon dioxide solution and the action time;

[0019] When the rate of decrease of microscopic indicators of cement with different formulations is stable, the numerical model analysis is carried out;

[0020] This process obtains XRD mineral composition content changes, porosity and permeability.

[0021] Furthermore, step (5) models the time-dependent carbonization process of cement under simulated formation pressure stabilization conditions by using the chemical reaction engineering module of Comsol Multiphsics, specifically including:

[0022] First, set up the carbonation reaction in the reaction engineering interface. The carbonation reaction involves calcium feldspar and obtains calcite and kaolinite as reaction products. Its chemical reaction formula is:

[0023] CO2+CaAl2Si2O8+2H2O=CaCO3+AlSi2O5(OH) (4-1)

[0024] In a partially filled saturated porous medium, the partial differential equation for the conservation of CO2 mass is a time-dependent diffusion transport process, and its expression is as follows:

[0025]

[0026] In the formula, ci is its concentration, D is the diffusion coefficient, and Ri is the reaction rate expression;

[0027] The above equation is obtained by conservation of the CO2 mass flux vector Ni, starting from the first Fick's law of diffusion of specimens in dilute solution, in the absence of convection mechanisms:

[0028]

[0029] The conservation equations are calculated as the concentration of water per cubic volume in the porous medium. This feature is set up in comsolMultiphysics using the Partially Saturated Porous Medium definition:

[0030] For cement stone carbonation simulation, the CO2 diffusion coefficient D c The determination of the carbonization reaction rate r of CO2 is the most important, and the diffusion coefficient D c and carbonization reaction rate r represent the two processes of CO2 erosion of cement paste: D c It reflects the stage of CO2 diffusion into cement paste, which is affected by the internal pores of cement paste and the penetration rate of CO2. The carbonation reaction rate r reflects the stage of CO2 entering into cement paste and reacting with the alkaline substances in cement paste, which is affected by factors such as temperature and alkaline substance content:

[0031] Calculate the value of the parameter

[0032] D c The assignment rules of and r are as follows:

[0033] D c Values:

[0034] D c =D c,0 F1(T)F2(H)F3(η)F4(σ) (4-4)

[0035] (1)D c,0 :CO2 diffusion coefficient of cement stone before carbonization:

[0036]

[0037] Where, W / C is the water-cement ratio of cement paste, which is 0.48;

[0038] H ref - Reference relative humidity inside cement stone is 78%;

[0039] F1(T): Function of the effect of temperature on CO2 diffusion coefficient:

[0040]

[0041] Where, E is the energy consumed by the reaction of 1 mol CO2, and E = 21800 (J / mol);

[0042] R—molar gas constant, take R=8.314 (J / mol k);

[0043] T ref —Reference temperature, i.e., the temperature at which D is measured c,0 The average temperature is generally 296.8K;

[0044] T is the temperature at which cement stone is carbonized. In the rapid carbonization experiment of concrete, the temperature of the carbonization box is (100±2)℃. Taking T=100℃, the Kelvin temperature converted into thermodynamics is 100+273.15=373.15K.

[0045] F2(H): Influence function of ambient humidity on CO2 diffusion coefficient of cement paste;

[0046] F2(H)=(1-H) 2.5 (4-7)

[0047] Where, H is relative ambient humidity. In the cement stone rapid carbonization test, the humidity of the carbonization box is (70±5)%, so H is taken as 70%.

[0048] F3(η): Function of the influence of cement paste carbonation degree on cement paste CO2 diffusion coefficient:

[0049]

[0050] Where: η is the carbonation degree of cement paste. When the cement paste is not carbonized, η=0; when the cement paste is completely carbonized, η=1.

[0051] F4(σ): Function of the influence of stress on the CO2 diffusion coefficient of cement paste:

[0052]

[0053] Where: S c —Compressive stress level coefficient:

[0054] The value of carbonization reaction rate r

[0055] The expression of r is:

[0056] D c =r0f1(T)f2(H) (4-10)

[0057] (1) r0: Carbonation reaction rate of cement paste under ideal conditions, r = 2.80 × 10 -7 / s·mol

[0058] (2) f1(T): the effect of temperature on the carbonation reaction rate of cement paste;

[0059]

[0060] Where: U0-the ratio of cement stone carbonization activation energy to gas constant, U0=11.25KJ / mol;

[0061] R—molar gas constant,

[0062] T is the temperature of cement paste during carbonization reaction. In the concrete rapid carbonization experiment, the temperature of the carbonization box is (100±2)℃, so T=100℃;

[0063] f2(H): Function of the effect of humidity on the carbonation reaction rate of cement paste;

[0064]

[0065] Where, H is the ambient humidity;

[0066] The relative strength of the anti-corrosion cement will eventually be damaged as the corrosion time goes by, resulting in a decrease in the bearing capacity of the cement sheath and a gradual loss of mechanical integrity. Therefore, the strength life prediction of the anti-corrosion cement is also an important aspect of the wellbore integrity analysis of the cement sheath. This requires the establishment of the relationship between the damage degree of the mechanical properties of the cementing cement stone and the corrosion time under the conditions of carbon dioxide geological storage. According to the theory of continuous damage mechanics, the mechanism of the degradation of the mechanical properties of the material is the reduction of the effective bearing area caused by defects, which is also the prototype and basis of various other damage theories. Therefore, it can be considered that the mechanical strength damage of the cementing cement stone after carbon dioxide corrosion is caused by the change in material properties caused by corrosion and the accumulation of internal defects. Therefore, the relationship between the damage degree of the mechanical strength of the cement stone and the corrosion time is essentially a process in which the mechanical strength of the cement stone changes with the increase of corrosion time and the increase of corrosion depth. The function expressions are shown in (5-1) and (5-2). The relationship between corrosion depth and corrosion time conforms to L=αt 1 / 2 Therefore, the relationship between strength damage and depth can be obtained to obtain the relationship between strength damage and corrosion time:

[0067] D=F(L) (5-1)

[0068] L=H(t) (5-2)

[0069] Where, D—strength damage degree, %;

[0070] L—corrosion depth, mm;

[0071] t_—corrosion time, d;

[0072] F—the functional relationship between strength damage and corrosion depth;

[0073] H—the functional relationship between corrosion depth and corrosion time;

[0074] Assuming that the corrosion progresses uniformly and the bearing surface of the specimen does not change during the corrosion process, that is, there is no expansion or peeling, when the corrosion depth is L, the absolute damage degree of the specimen after corrosion can be expressed as:

[0075]

[0076] Where D cos —Absolute degree of damage;

[0077] A load — bearing area;

[0078] A0—the area of ​​the uncorroded part;

[0079] D0—Damage degree of the uncorroded part, damage caused by the original porosity inside the cement paste;

[0080] A L —The area of ​​the corroded part when the corrosion depth is L;

[0081] D L —Degree of damage of the corroded part when the corrosion depth is L;

[0082] The corrosion layer of cement stone after carbon dioxide corrosion has a layered structure, so it is necessary to further divide the corrosion layer. Since the thickness of the calcium hydroxide dissolution layer is small, the entire corrosion layer can be considered to be mainly composed of two parts: one is the external leached decalcification layer with increased porosity and reduced strength, and the other is the internal carbonized dense layer with reduced porosity and increased strength. Therefore, formula (5-3) can be changed to:

[0083]

[0084] Where, A1 is the area of ​​carbonized dense layer;

[0085] D1—damage degree of carbonized dense layer;

[0086] A2—the area of ​​the leaching and decalcification layer;

[0087] D L —Degree of damage to the leached decalcified layer.

[0088] Assume that when the corrosion time is t, the ratio coefficient of the depth of the leached decalcified layer to the total corrosion depth is β; then, A0, A1, and A2 can be expressed as:

[0089] A0=π(RL) 2 (5-5)

[0090] A1=π(R-(1-β)L) 2 -A0=π(R-(1-β)L) 2 -π(RL) 2 (5-6)

[0091] A2=πR 2 -π(R-βL) 2 (5-7)

[0092] Substituting equation (5-5) and equation (5-7) into equation (5-4) and combining similar terms, we can obtain:

[0093]

[0094] When the corrosion conditions and sample material conditions are constant, D0, D1, D2, and β in the formula can be regarded as constants, so formula (5-8) can be changed to:

[0095]

[0096] Where α and b are test coefficients related to corrosion conditions and sample material conditions;

[0097] The following two pieces of information can be analyzed from formula (5-9): First, the absolute damage degree of cement paste after corrosion is related to the original damage degree of the material. The more pores and looser the structure inside the material, the greater the original damage degree. Therefore, reducing the original damage inside the cement paste through relevant technical means is a way to improve the corrosion resistance of cement paste. Second, the damage degree of cement paste can also be regarded as a function of relative corrosion depth (L / R), which shows that the corrosion damage degree of cement paste is not only related to the corrosion depth or corrosion rate but also to the size of the cement paste sample. This is not difficult to understand. Under the same corrosion depth conditions, the larger the size of the cement paste, the smaller the influence of the corrosion layer. Therefore, appropriately increasing the thickness of the cementing cement ring through reasonable wellbore structure design is also an important way to increase the corrosion life of the cementing cement ring.

[0098] For a sample with known dimensions and R, equation (5-9) can be rewritten as:

[0099] D cos =D0+mL+nL 2 (5-10)

[0100] D0 represents the original damage inside the cement paste before corrosion. However, this value is often difficult to obtain accurately. In engineering, people are generally more concerned about the relative damage degree D of the cement paste before and after corrosion, that is, the damage caused by corrosion. Therefore, according to formula (5-10), the relative damage degree D can be expressed as:

[0101] D=D cos -D0+nL+mL 2 (5-11)

[0102] The intercept in formula (5-11) is 0, indicating that when the corrosion depth is 0, the corrosion damage of cement paste is 0. Taking cement paste with a liquid-to-solid ratio of 0.44 under corrosion conditions of 60°C, CO2 pressure of 20MPa as an example, the variation of its compressive strength damage and tensile strength damage with corrosion depth and the fitting of quadratic curves are all above 90%, indicating that the quadratic curve can better reflect the relationship between strength damage and corrosion depth.

[0103] The relationship between the corrosion depth L and the corrosion time t is L = αt 1 / 2 Substituting into formula (5-11) we can get:

[0104] D=nα 2 t+mαt 1 / 2 (5-12)

[0105] Let nα 2 =N,mα=M, then equation (5-12) can be simplified to:

[0106] D=Nt+Mt 1 / 2 (5-13)

[0107] Using data processing software, through its self-compiled fitting function, equation (5-13) was incorporated into the Abaqus software to establish a cement stone damage model affected by carbonization corrosion and carry out subsequent research.

[0108] Furthermore, in step (6), the three indicators of mechanical index, microstructure and numerical model account for the same proportion, that is, 1 / 3 each. The comprehensive score of standard formula cement is F0, and the mechanical index score is defined as The compressive strength score is defined as The tensile strength score is defined as The breakthrough stress score is defined as The microstructural index score is defined as The XRD mineral composition content index score is defined as The porosity score is defined as The penetration score is defined as The numerical model score is defined as The comprehensive score F of cement to be compared with the standard formula, and the mechanical index score is defined as F n , the compressive strength score is defined as The tensile strength score is defined as The breakthrough stress score is defined as The microstructure index score is defined as F m , the XRD mineral composition content index score is defined as F xr , the porosity score is defined as The permeability score is defined as F k; The numerical model score is defined as F s .

[0109] F=F n +F m +F s (1)

[0110]

[0111]

[0112] Beneficial effects of the present invention:

[0113] (1) Using the carbon dioxide corrosion resistance evaluation method, the carbon dioxide corrosion resistance evaluation speed of oil well cement can be further improved.

[0114] (2) The existing technology only evaluates the carbon dioxide corrosion resistance of oil well cement from mechanical indicators or microscopic indicators, which can only analyze its macroscopic characteristics or microscopic characteristics and cannot obtain a comprehensive evaluation result. Therefore, it is necessary to combine mechanical, microscopic and numerical simulation to evaluate the carbon dioxide corrosion resistance of oil well cement more comprehensively and accurately from micro to macro.

[0115] (3) The corrosion evolution model can be used to reasonably predict the corrosion performance of cement in unknown environments. BRIEF DESCRIPTION OF THE DRAWINGS

[0116] Figure 1 It is the technical roadmap of the present invention;

[0117] Figure 2 To prefabricate cement samples of different formulations using a mixer and a high temperature curing device under high temperature conditions, wherein (a) is a mixer, (b) is a high temperature curing device, (c) is a cement sample cured in water for 28 days, and (d) is a prefabricated cement sample;

[0118] Figure 3 Schematic diagram of the control device and reactor structure, where (a) is the temperature control device and (b) is the reactor;

[0119] Figure 4 This is a schematic diagram of a carburization corrosion sample;

[0120] Figure 5(a) is a graph showing the carbonization depth versus time obtained by the numerical model;

[0121] Figure 5(b) shows the change of cement carbonization depth at different corrosion times in the laboratory;

[0122] Figure 6(a) is a schematic diagram of CO2 input parameters;

[0123] Figure 6(b) shows the CO2 input boundary;

[0124] Figure 7(a) is a cloud diagram of the carbonation depth of cement after 7 days of corrosion;

[0125] Figure 7(b) is a cloud diagram of the carbonation depth of cement after 60 days of corrosion;

[0126] Figure 7(c) is a cloud diagram of the carbonation depth of cement after 120 days of corrosion. DETAILED DESCRIPTION

[0127] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention is described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0128] Example

[0129] like Figure 1 As shown, cement samples with different formulations were prefabricated under high temperature conditions, and the samples were immersed in carbon dioxide solution for different time periods. The change patterns of breakthrough pressure, shear resistance and tensile strength of cement under simulated formation temperature and pressure conditions were studied under different corrosion conditions. The change patterns of various indicators with the action time of carbon dioxide solution were analyzed, a corrosion evolution model was constructed, and the corrosion mechanism was revealed.

[0130] For example, the slower the compressive strength decreases with the increase of immersion time, the better the cement's resistance to carbon dioxide corrosion. The same principle applies to other indicators. If the rate of decrease of mechanical indicators of cements with different formulations is basically the same (after the rate of decrease of mechanical indicators of cements with different formulations is stable, microstructure analysis can be performed), microstructure analysis can be performed to study the change of pore permeability and XRD with immersion time. If the porosity or permeability increases more slowly with the increase of immersion time, the better the cement's resistance to carbon dioxide corrosion. If the content of Ca(OH)2 decreases more slowly with the increase of immersion time. At the same time, the slower the increase of CaCO3 content, the smaller the reaction of carbon dioxide with the cement, and the stronger the resistance to carbon dioxide corrosion. If the rate of change of microscopic indicators of cements with different formulations is basically the same (after the rate of decrease of microscopic indicators of cements with different formulations is stable, microstructure analysis can be performed), numerical simulation analysis can be performed to model the time-dependent carbonization process of cement using the chemical reaction engineering module of Comsol Multiphysics, simulate the carbonization process of cement, and predict the change of cement carbonization depth with time. If the carbonization depth increases more slowly with the immersion time, it means that the cement has better resistance to carbon dioxide corrosion.

[0131] Example

[0132] like Figure 1 , Figure 2 As shown, the formula ratio of prefabricated protective cement under high temperature conditions is: cement 704.16g + clean water 264.43g + fluid loss reducer 33.41g + defoaming agent 1.76g; G grade cement ratio: cement 700g + clean water 280g + fluid loss reducer 28g + defoaming agent 1.75g.

[0133] Add the sample to Figure 3 In the reactor shown in (b), an excess of saline solution from the deep saline layer in the target area is added to completely submerge the sample involved in the reaction, the reactor is closed, and the pipeline for CO2 is connected. Figure 3 The temperature control device shown in (a) heats the reactor. When the reactor reaches the target temperature, the valve is opened and CO2 is injected into the reactor through the booster device (main pump and booster pump). When the reactor reaches the target temperature (95°C) and the target pressure (17MPa) and remains constant, the high temperature and high pressure static carburization corrosion reaction test is started, in which the carburization corrosion time is controlled for 7 days, 14 days, 30 days, 45 days, 60 days and 90 days respectively.

[0134] When the high temperature and high pressure static carbonization corrosion reaction is completed, first close the temperature control device to lower the temperature of the reactor to room temperature, then discharge the CO2 in the reactor from the exhaust port of the main pump of the booster device, open the reactor, and obtain the reaction sample after the carbonization corrosion reaction is completed (such as Figure 4 as shown) and the reaction solution.

[0135] Table 1 Summary of triaxial compression test results of grade G cement

[0136]

[0137] Table 2 Summary of triaxial compression test results of anticorrosive cement

[0138]

[0139] The compressive strength will change with the increase of immersion time. The cement ratio of the two cement samples changes at different rates. The smaller the rate, the better the corrosion resistance evaluation of the formula. Therefore, the anti-corrosion cement formula has better corrosion resistance.

[0140] Table 3 Experimental results of G grade cement

[0141]

[0142] Table 4 Anticorrosive cement test results

[0143]

[0144] The tensile strength will change with the increase of immersion time. The cement ratios of different formulas change at different rates. The smaller the rate, the better the corrosion resistance of the formula. Therefore, the anti-corrosion cement formula has better corrosion resistance.

[0145] Table 5 Mineral composition of G grade cement

[0146]

[0147] Among them, the CaCO3 of Grade G cement at 0 days is 10.35%, the CaCO3 at 30 days is 21.79%, and the CaCO3 at 45 days is 31.78%. The content at 30 days is increasing by 110.5% compared with that at 0 days, and the average daily increase is 110.5 / 30=3.68%; the content at 45 days is increasing by 45.8% compared with that at 30 days, and the average daily increase is 3.05%, which is 0.63% less than before.

[0148] Table 6 Mineral composition of anticorrosive cement

[0149]

[0150] The CaCO3 of the anticorrosive cement is 12.17% at 0 days, 36.42% at 30 days, and 45.50% at 45 days. The content of 30 days is increasing by 199.2% compared with 0 days, and the average daily increase is 199.2 / 30=6.64%; the content of 45 days is increasing by 24.9% compared with 30 days, and the average daily increase is 1.66%. It is 6.64-1.66=4.98% less than before, and the anticorrosive cement has a greater reduction rate, so the anticorrosive cement has better corrosion resistance.

[0151] Therefore, by analyzing the microstructure of cement's resistance to carbon dioxide: the changes in mineral composition, that is, the changes in component content of XRD results, especially the changes in the content of CaCO3, the slower the change with the increase of immersion time, the smaller the reaction between carbon dioxide and cement of this formula, and the stronger the resistance to carbon dioxide corrosion.

[0152] Table 7 is the breakthrough pressure test result table, where 1-1, 1-2, 1-4, ..., those starting with 1, represent Grade G cement, and 2-1, 2-2, 2-4, ..., those starting with 2, represent anti-corrosion cement.

[0153]

[0154] The breakthrough pressure will change with the increase of immersion time. The change speed of cement with different formulas is different. The smaller the speed, the better the corrosion resistance evaluation of the formula. Therefore, the corrosion-resistant cement has better corrosion resistance.

[0155] Table 8 Porosity test results

[0156]

[0157]

[0158] As can be seen from the above table, the porosity will change with the increase of immersion time. The change speed of cement with different formulas is different. The smaller the speed, the better the corrosion resistance evaluation of the formula. Therefore, the corrosion-resistant cement has better corrosion resistance.

[0159] Table 9 Permeability test results

[0160]

[0161] From the above table, the permeability will change with the increase of immersion time. The change speed of cement with different formulas is different. The smaller the speed, the better the corrosion resistance evaluation of the formula. Therefore, the corrosion resistance evaluation of the anti-corrosion cement is better.

[0162] As shown in Figure 5(a) and Figure 5(b), the relationship between the change of carbonation depth and time is obtained by using the numerical model. The results show that the carbonation rate slows down with the increase of time, and it can be seen that there is a linear relationship between the carbonation depth of the numerical model and the power of half of the time, which is consistent with the results of the cement samples in the laboratory. With the increase of immersion time, the carbonation depth of the numerical model increases. The increasing speed of cement with different formulas is different. The slower the speed, the stronger the corrosion resistance of the cement with this formula. Therefore, the corrosion resistance of the anti-corrosion cement is better.

[0163] The numerical model is established as follows:

[0164] In order to simulate the carbonation process of cement sheath and cement plug and predict the change of cement carbonation depth over time, the present invention models the time-dependent carbonation process of cement sheath by using the chemical reaction engineering module of Comsol Multiphysics. The modeling process is as follows: first, the carbonation reaction is set in the reaction engineering interface. The carbonation reaction involves calcium feldspar and obtains calcite and kaolinite as reaction products. The chemical reaction formula is:

[0165] CO2+CaAl2Si2O8+2H2O=CaCO3+AlSi2O5(OH) (4-1)

[0166] In a partially filled saturated porous medium, the partial differential equation for the conservation of CO2 mass is a time-dependent diffusion transport process, and its expression is as follows:

[0167]

[0168] In the formula, ci is its concentration, D is the diffusion coefficient, and Ri is the reaction rate expression;

[0169] The above equation is obtained by conservation of the CO2 mass flux vector Ni, starting from the first Fick's law of diffusion of specimens in dilute solution, in the absence of convection mechanisms:

[0170]

[0171] The conservation equations are calculated in terms of the concentration of water per cubic volume in the porous medium. This feature can be set up in comsolMultiphysics by using the Partially Saturated Porous Medium Definition.

[0172] For cement stone carbonation simulation, the CO2 diffusion coefficient D c The determination of the carbonization reaction rate r of CO2 is the most important. Diffusion coefficient D c and carbonization reaction rate r represent the two processes of CO2 erosion of cement paste: D c It reflects the stage of CO2 diffusion into cement paste, which is affected by the internal pores of cement paste and the penetration rate of CO2. The carbonation reaction rate r reflects the stage of CO2 entering into cement paste and reacting with the alkaline substances inside cement paste, which is affected by factors such as temperature and the content of alkaline substances.

[0173] Calculate the value of the parameter

[0174] D c The assignment rules of and r are as follows:

[0175] D c Values:

[0176] D c =D c,0 F1(T)F2(H0F3(η)F4(σ0 (4-4)

[0177] (1)D c,0 :CO2 diffusion coefficient of cement stone before carbonization:

[0178]

[0179] Where, W / C is the water-cement ratio of cement paste, which is 0.48;

[0180] H ref - Reference relative humidity inside cement stone is 78%;

[0181] F1(T): Function of the effect of temperature on CO2 diffusion coefficient:

[0182]

[0183] Where, E is the energy consumed by the reaction of 1 mol CO2, and E = 21800 (J / mol);

[0184] R—molar gas constant, take R=8.314 (J / mol k);

[0185] T ref —Reference temperature, i.e., the temperature at which D is measured c,0 The average temperature is generally 296.8K;

[0186] T is the temperature at which cement stone is carbonized. In the rapid carbonization experiment of cement stone, the temperature of the carbonization box is (100±2)℃. Taking T=100℃, the Kelvin temperature converted into thermodynamics is 100+273.15=373.15K.

[0187] F2(H): Influence function of ambient humidity on CO2 diffusion coefficient of cement paste;

[0188] F2(H)=(1-H) 2.5 (4-7)

[0189] Where, H is relative ambient humidity. In the cement stone rapid carbonization test, the humidity of the carbonization box is (70±5)%, so H is taken as 70%.

[0190] F3(η): Function of the influence of cement paste carbonation degree on cement paste CO2 diffusion coefficient:

[0191]

[0192] Where: η is the carbonation degree of cement paste. When the cement paste is not carbonized, η=0; when the cement paste is completely carbonized, η=1.

[0193] F4(σ): Function of the influence of stress on the CO2 diffusion coefficient of cement paste:

[0194]

[0195] Where: S c —Compressive stress level coefficient.

[0196] The value of carbonization reaction rate r

[0197] The expression of r is:

[0198] D c =r0f1(T)f2(H) (4-10)

[0199] (1) r0: Carbonation reaction rate of cement paste under ideal conditions, r = 2.80 × 10 -7 / s·mol

[0200] (2) f1(T): the effect of temperature on the carbonation reaction rate of cement paste;

[0201]

[0202] Where: U0-the ratio of concrete carbonization activation energy to gas constant, U0=11.25KJ / mol;

[0203] R—molar gas constant,

[0204] T is the temperature of cement paste during carbonization reaction. In the rapid carbonization experiment of cement paste, the temperature of the carbonization box is (100±2)℃, so T=100℃.

[0205] f2(H): Function of the effect of humidity on the carbonation reaction rate of cement paste;

[0206]

[0207] Where, H is the ambient humidity.

[0208] As shown in Figure 6(a) and Figure 6(b), it can be seen from the above test results that the relative strength of the anti-corrosion cement will eventually be damaged with the corrosion time, resulting in a decrease in the bearing capacity of the cement sheath and a gradual loss of mechanical integrity. Therefore, the strength life prediction of the anti-corrosion cement is also an important aspect of the wellbore integrity analysis of the cement sheath. This requires the establishment of the relationship between the damage degree of the mechanical properties of cementing cement stone and the corrosion time under the conditions of carbon dioxide geological storage. According to the theory of continuous damage mechanics, the mechanism of the degradation of the mechanical properties of materials is the reduction of the effective bearing area caused by defects, which is also the prototype and basis of various other damage theories. It can be considered that the mechanical strength damage of cementing cement stone after carbon dioxide corrosion is caused by the change of material properties caused by corrosion and the accumulation of internal defects. Therefore, the relationship between the damage degree of the mechanical strength of cement stone and the corrosion time is essentially a process in which the mechanical strength of cement stone changes with the increase of corrosion time and the increase of corrosion depth. The functional expressions are shown in (5-1) and (5-2). The relationship between corrosion depth and corrosion time conforms to L=αt 1 / 2 Therefore, the relationship between strength damage and depth can be obtained to obtain the relationship between strength damage and corrosion time.

[0209] D=F(L) (5-1)

[0210] L=H(t) (5-2)

[0211] Where, D—strength damage degree, %;

[0212] L—corrosion depth, mm;

[0213] t—corrosion time, d;

[0214] F—the functional relationship between strength damage and corrosion depth;

[0215] H—The functional relationship between corrosion depth and corrosion time.

[0216] Assuming that the corrosion progresses uniformly and the bearing surface of the specimen does not change during the corrosion process, that is, there is no expansion or peeling, when the corrosion depth is L, the absolute damage degree of the specimen after corrosion can be expressed as:

[0217]

[0218] Where D cos —Absolute degree of damage;

[0219] A load — bearing area;

[0220] A0—the area of ​​the uncorroded part;

[0221] D0—Damage degree of the uncorroded part, damage caused by the original porosity inside the cement paste;

[0222] A L —The area of ​​the corroded part when the corrosion depth is L;

[0223] D L —Degree of damage of the corroded part when the corrosion depth is L.

[0224] The corrosion layer of cement stone after carbon dioxide corrosion has a layered structure, so it is necessary to further divide the corrosion layer. Since the thickness of the calcium hydroxide dissolution layer is small, the entire corrosion layer can be considered to be mainly composed of two parts: one is the external leaching decalcification layer with increased porosity and reduced strength, and the other is the internal carbonized dense layer with reduced porosity and increased strength. Therefore, formula (5-3) can be changed to:

[0225]

[0226] Where, A1 is the area of ​​carbonized dense layer;

[0227] D1—damage degree of carbonized dense layer;

[0228] A2—the area of ​​the leaching and decalcification layer;

[0229] D L —Degree of damage to the leached decalcified layer.

[0230] Assume that when the corrosion time is t, the ratio coefficient of the depth of the leached decalcified layer to the total corrosion depth is β. Then, A0, A1, and A2 can be expressed as:

[0231] A0=π(RL)2 (5-5)

[0232] A1=π(R-(1-β)L) 2 -A0=π(R-(1-β)L) 2 -π(RL) 2 (5-6)

[0233] A2=πR 2 -π(R-βL) 2 (5-7)

[0234] Substituting equation (5-5) and equation (5-7) into equation (5-4) and combining similar terms, we can obtain:

[0235]

[0236] When the corrosion conditions and sample material conditions are constant, D0, D1, D2, and β in the formula can be regarded as constants, so formula (5-8) can be changed to:

[0237]

[0238] Where α and b are test coefficients related to corrosion conditions and sample material conditions.

[0239] The following two pieces of information can be analyzed from formula (5-9): First, the absolute damage degree of cement paste after corrosion is related to the original damage degree of the material. The more pores and looser the structure inside the material, the greater the original damage degree. Therefore, reducing the original damage inside the cement paste through relevant technical means is a way to improve the corrosion resistance of cement paste; secondly, the damage degree of cement paste can also be regarded as a function of relative corrosion depth (L / R), which shows that the corrosion damage degree of cement paste is not only related to the corrosion depth or corrosion rate, but also to the size of the cement paste sample. This is not difficult to understand. Under the same corrosion depth conditions, the larger the size of the cement paste, the smaller the influence of the corrosion layer. Therefore, appropriately increasing the thickness of the cementing cement ring through reasonable wellbore structure design is also an important way to increase the corrosion life of the cementing cement ring.

[0240] For a sample with known dimensions and R, equation (5-9) can be rewritten as:

[0241] D cos =D0+mL+nL 2 (5-10)

[0242] D0 represents the original damage inside the cement paste before corrosion. However, this value is often difficult to obtain accurately. In engineering, people are generally more concerned about the relative damage degree D of the cement paste before and after corrosion, that is, the damage caused by corrosion. Therefore, according to formula (5-10), the relative damage degree D can be expressed as:

[0243] D=D cos -D0+nL+mL 2 (5-11)

[0244] The intercept in formula (5-11) is 0, indicating that when the corrosion depth is 0, the corrosion damage of cement paste is 0. Taking cement paste with a liquid-to-solid ratio of 0.44 under corrosion conditions of 60°C, CO2 pressure of 20MPa as an example, the variation of its compressive strength damage and tensile strength damage with corrosion depth and the fitting of quadratic curves are all above 90%, indicating that the quadratic curve can better reflect the relationship between strength damage and corrosion depth.

[0245] The relationship between the corrosion depth L and the corrosion time t is L = αt 1 / 2 Substituting into formula (5-11) we can get:

[0246] D=nα 2 t+mαt 1 / 2 (5-12)

[0247] Let nα 2 =N,mα=M, then equation (5-12) can be simplified to:

[0248] D=Nt+Mt 1 / 2 (5-13)

[0249] Using data processing software, through its self-compiled fitting function, equation (5-13) was incorporated into the Abaqus software to establish a cement stone damage model affected by carbonization corrosion and carry out subsequent research.

[0250] Multiple indicators combined evaluation:

[0251] From the empirical formula, it can be obtained that the three indicators of mechanics, microstructure and numerical model each account for the same score, that is, each accounts for 1 / 3; the score of mechanical indicators is determined by compressive strength, tensile strength and breakthrough pressure, and each accounts for 1 / 3 of the mechanical indicators, that is, compressive strength, tensile strength and breakthrough pressure indicators each account for 1 / 9 of the total indicators; microstructure indicators are determined by XRD mineral composition content changes, porosity and permeability, and each accounts for 1 / 3 of the microstructure indicators, that is, SRD mineral composition content changes, porosity and permeability account for 1 / 9 of the total indicators; numerical model indicators account for 1 / 3 of the total indicators. For example, after the same corrosion time under the same stable pressure conditions, the mechanical indicators and numerical model indicators of formula 1 cement are better, and the microstructure indicators are slightly worse. Then, the formula 1 cement accounts for 2 / 3*100=67 points, and the formula 2 cement accounts for 1 / 3*100=33 points. The formula 1 cement has a better score, indicating that the comprehensive evaluation of the carbon dioxide corrosion resistance of the formula 1 cement is better.

[0252] In step (6), the three indicators of mechanical index, microstructure and numerical model account for the same proportion, that is, 1 / 3 each. The comprehensive score of standard formula cement is F0, and the mechanical index score is defined as The compressive strength score is defined as The tensile strength score is defined as The breakthrough stress score is defined as The microstructural index score is defined as The XRD mineral composition content index score is defined as The porosity score is defined as The penetration score is defined as The numerical model score is defined as The comprehensive score F of cement to be compared with the standard formula, and the mechanical index score is defined as F n , the compressive strength score is defined as The tensile strength score is defined as The breakthrough stress score is defined as The microstructure index score is defined as F m , the XRD mineral composition content index score is defined as F xr , the porosity score is defined as The permeability score is defined as F k ; The numerical model score is defined as F s .

[0253] F=F n +F m +F s (1)

[0254]

[0255] In Figure 7(a), Figure 7(b), and Figure 7(c), red represents the maximum value of the CO2 concentration distribution in the cement paste, yellow and green represent the larger values ​​of the CO2 concentration distribution in the cement paste, and blue represents the minimum value of the CO2 concentration distribution in the cement paste. In the three cloud maps, CO2 continuously penetrates into the cement paste from the boundary. The CO2 on the surface of the cement paste is large, and the interior of the cement paste is basically blue, with the lowest CO2 concentration. Analysis shows that the CO2 concentration value inside the cement paste, that is, the value at the front end of CO2 diffusion, can directly reflect the CO2 concentration in the cement paste, that is, the degree of carbonization. As can be seen from the figure, as the carbonization time increases at the reaction site, the CO2 concentration inside the cement paste gradually increases, which is in line with the experimental research law.

[0256] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for evaluating the carbon dioxide corrosion resistance of oil well cement, characterized in that: include: Step (1). Sample preparation. At least three samples of each type need to be prepared. Step (2). Long-term corrosion of cement, the corrosion time is at least 7 days; Step (3). Microstructure and mechanical index testing; Mechanical index testing refers to the analysis of the changes in the physical and mechanical indexes of breakthrough pressure, compression, shear and tensile strength of oil well cement under simulated formation temperature and pressure conditions, and the construction of a corrosion evolution model by analyzing the changes in various indexes with the concentration of carbon dioxide solution and the action time; When the rate of decrease of mechanical indicators of cements with different formulations is stable, microstructural analysis is carried out; And obtain the compressive strength, tensile strength and breakthrough pressure values; Microstructure analysis refers to the study of the change rules of oil well cement under simulated formation pressure stabilization conditions, porosity, permeability and XRD test, and the analysis of the change rules of various indicators with the concentration of carbon dioxide solution and the action time; When the rate of decrease of microscopic indicators of cement with different formulations is stable, the numerical model analysis is carried out; And obtain XRD mineral composition content changes, porosity and permeability values; Step (4). Carbonization depth test; Step (5). Establishing a numerical model; The time-dependent carbonization process of oil well cement under simulated formation pressure stabilization conditions is modeled using the chemical reaction engineering module of ComsolMultiphsics, including: First, set up the carbonation reaction in the reaction engineering interface. The carbonation reaction involves calcium feldspar and obtains calcite and kaolinite as reaction products. Its chemical reaction formula is: CO2+CaAl2Si2O8+2H2O=CaCO3+AlSi2O5(OH) (4-1) In a partially filled saturated porous medium, the partial differential equation for the conservation of CO2 mass is a time-dependent diffusion transport process, and its expression is as follows: In the formula, ci is its concentration, D is the diffusion coefficient, and Ri is the reaction rate expression; The above equation is obtained by conservation of the CO2 mass flux vector Ni, starting from the first Fick's law of diffusion of specimens in dilute solution, in the absence of convection mechanisms: The conservation equations are calculated in terms of the concentration of water per cubic volume in the porous medium, which is set up in Comsol Multiphysics using the partially saturated porous medium definition: For cement stone carbonation simulation, the CO2 diffusion coefficient D c The determination of the carbonization reaction rate r of CO2 is the most important, and the diffusion coefficient D c and carbonization reaction rate r represent the two processes of CO2 erosion of cement paste: D c It reflects the stage of CO2 diffusion into cement paste, which is affected by the internal pores of cement paste and the penetration rate of CO2; the carbonation reaction rate r reflects the stage of CO2 entering into cement paste and reacting with the alkaline substances in cement paste, which is affected by temperature and alkaline substance content: Calculate the value of the parameter D c The assignment rules of and r are as follows: D c Values: D c =D c,0 F1(T)F2(H)F3(η)F4(σ) (4-4) (1)D c,0 :CO2 diffusion coefficient of cement stone before carbonization: Where, W / C is the water-cement ratio of cement paste, which is 0.48; H ref - Reference relative humidity inside cement stone is 78%; F1(T): Function of the effect of temperature on CO2 diffusion coefficient: In the formula, E is the energy consumed by the reaction of 1 mol CO2, and E = 21800 J / mol; R—molar gas constant, take R=8.314J / molk; T ref —Reference temperature, i.e., the temperature at which D is measured c,0 The average temperature is 296.8K; T——the temperature of cement paste during carbonization. In the rapid carbonization experiment of cement paste, the temperature of the carbonization box is 100±2℃. Taking T=100℃, the Kelvin temperature in thermodynamics is 100+273.15=373.15K. F2(H): Influence function of ambient humidity on CO2 diffusion coefficient of cement paste; F2(H)=(1-H) 2.5 (4-7) Where, H is relative ambient humidity; in the cement paste rapid carbonization test, the humidity of the carbonization box is 70±5%, so H is taken as 70%; F3(η): Function of the influence of cement paste carbonation degree on cement paste CO2 diffusion coefficient: Where: η is the carbonation degree of cement paste. When the cement paste is not carbonized, η=0; when the cement paste is completely carbonized, η=1. F4(σ): Function of the influence of stress on the CO2 diffusion coefficient of cement paste: Where: S c —Compressive stress level coefficient: The value of carbonization reaction rate r The expression of r is: r=r0f1(T)f2(H) (4-10) (1) r0: Carbonation reaction rate of cement paste under ideal conditions, r = 2.80 × 10 -7 / s·mol (2) f1(T): the effect of temperature on the carbonation reaction rate of cement paste; Where: U0-the ratio of cement stone carbonization activation energy to gas constant, U0=11.25KJ / mol; R—molar gas constant, T is the temperature of cement paste during carbonization reaction. In the rapid carbonization experiment of cement paste, the temperature of the carbonization box is 100±2℃, so T=100℃; f2(H): Function of the effect of humidity on the carbonation reaction rate of cement paste; Where, H is the ambient humidity; Step (6). Comprehensive evaluation based on mechanical indexes, microstructure and numerical simulation of carbonization depth changes; In step (6), the three indicators of mechanical index, microstructure and numerical model account for the same proportion, that is, 1 / 3 each. The comprehensive score of standard formula cement is F0, and the mechanical index score is defined as The compressive strength score is defined as The tensile strength score is defined as The breakthrough stress score is defined as The microstructural index score is defined as The XRD mineral composition content index score is defined as The porosity score is defined as The penetration score is defined as The numerical model score is defined as The comprehensive score F of cement to be compared with the standard formula, and the mechanical index score is defined as F n , the compressive strength score is defined as The tensile strength score is defined as The breakthrough stress score is defined as The microstructure index score is defined as F m , the XRD mineral composition content index score is defined as F xr , the porosity score is defined as The permeability score is defined as F k ; The numerical model score is defined as F s : F=F n +F m +F s (1) 2. The method according to claim 1, characterized in that Step (2) also includes: putting the sample into a reaction kettle, pouring in groundwater, covering the kettle lid, injecting carbon dioxide into it, and then setting the temperature and pressure of the corresponding formation, and the temperature and pressure are set according to the working conditions.

Citation Information

Patent Citations

  • Method for evaluating corrosion status of well cement ring in acid gas reservoir well

    CN103091234A

  • Shale reservoir evaluation method based on rock test

    CN116842671A